Registered nurses' challenges and suggestions for improvement of their leadership close to older adults in municipal home healthcare - Erica Lillsjö; Kaisa Bjuresäter; Karin Josefsson (BMC, 2023)
Abstract Background Worldwide people are living longer. The need for healthcare for older adults is increasing. The trend is towards advanced home healthcare, where registered nurses are key figures. This implies challenges for municipal home healthcare, as well as for registered nurses' leadership. The aim is to explore registered nurses' perceptions of challenges and suggestions for improvements in their leadership close to older adults in municipal home healthcare. Methods The present study is part of a larger web-based questionnaire survey with a cross-sectional design. The design is inductive, analysing data using qualitative content analysis and descriptive statistics. A questionnaire with open-ended and closed-ended questions was used. A total of n = 70 registered nurses leading close to older adults participated in seven municipalities in two geographic areas in Sweden. Results The results show registered nurses' perceptions of challenges as leaders close to older adults in terms of 11 categories. The categories are motivating for care, adjusting and coordinating nursing care to the older adult, relating to next of kin, managing communication difficulties, relating to social situations in the home, managing demands, working alone, having lack of time, collaborating with physicians, and care staff having low competence. The registered nurses suggested improvements for their leadership close to older adults in terms of nine categories. The categories are adjusting the work to the older adult, clarifying registered nurses' responsibility, balancing demands and resources, setting time aside, improving staffs' competence, ensuring staff's competence development, improving the work environment, and cooperation between professions in the municipality, as well as between healthcare organizations. Conclusion The results show that registered nurses' leadership in municipal home healthcare implies a wide range of challenges. There is a need for strategies to improve the organizational preconditions to reduce challenges in registered nurses' leadership in order to promote positive patient outcomes for safe and quality care.